Biography of Banbhore Excavations:: A Personal Narrative - Mughal, Mohammad Rafique (Ancient Pakistan, 2022)
The paper is intended to emphasize that success of an archaeological field project also depends upon active support of several persons involved directly or indirectly in the excavations. Some persons who are designated variously, provide essential support, which collectively contributes to the success of a project. It also records enthusiasm, devotion and optimism of all participants who worked at a desolate place, lacking basic amenities of living but remained focused on learning techniques of archaeological excavations with hope for success.